Biomaterial-mediated delivery of traditional Chinese medicine ingredients for spinal cord injury: a systematic review - Liu, Gang; Pei, Zhenzhen; Bai, Huizhong; Huo, Luyao; Deng, Bowen; Jiang, Shengyuan; Tao, Jingwei; Xu, Lin; Li, Jinyu; Gao, Feng; Mu, Xiaohong (Frontiers in Pharmacology, 2024)
Biomaterials loaded with ingredients derived from traditional Chinese medicine (TCM) are viewed as a promising strategy for treating spinal cord injury (SCI). However, a comprehensive analysis of the existing literature on this topic has not yet been conducted. Therefore, this paper systematically reviews researches related to this approach, aiming to identify gaps and shortcomings in the field. We searched PubMed, EMBASE, Web of Science, Chinese Biomedical Literature, Wanfang, and China National Knowledge Infrastructure (CNKI). Results regarding biomaterials loaded with TCM ingredients were identified and searched, screened and manually classified for inclusion in this review. Six TCM ingredients-paclitaxel, curcumin, tetramethylpyrazine, resveratrol, berberine, and tanshinone IIA-were combined with biomaterials for treatment of SCI. Biomaterials were categorized into hydrogels, biodegradable scaffolds, nanoparticles, and microspheres according to the type of scaffold. These drug delivery systems exhibit commendable biocompatibility, drug-loading capacity, and drug-release capabilities, and in combination with TCM ingredients, synergistically contribute to anti-oxidative stress, anti-inflammatory, neuroprotective, and anti-apoptotic effects. These studies demonstrated the efficacy of biomaterials loaded with TCM ingredients in facilitating motor function recovery and neuroprotection in SCI rats, providing evidence for future research. However, in the complex microenvironment of SCI, achieving the maximum drug loading capacity of TCM ingredients within biomaterials, along with sustained and controlled release to fully exert their pharmacological effects, remains a major challenge for future research.